Respuesta :

gmany

[tex]f(x)=2x-5,\ g(x)=x^2-4x-8\\\\(f+g)(x)=f(x)+g(x)=(2x-5)+(x^2-4x-8)\\\\=2x-5+x^2-4x-8=x^2+(2x-4x)+(-5-8)=x^2-2x-13[/tex]

Answer:

[tex]\text{The value of (f+g)(x) is }x^2-2x-13[/tex]

Step-by-step explanation:

Given the two functions

[tex]f(x)=2x-5[/tex]

[tex]g(x)=x^2-4x-8[/tex]

we have to find the value of (f+g)(x)

As we know

[tex](f+g)(x)=f(x)+g(x)=(2x-5)+(x^2-4x-8)[/tex]

[tex]=2x-5+x^2-4x-8[/tex]

[tex]=x^2+2x-4x-5-8=x^2-2x-13[/tex]

[tex]\text{Hence, the value of (f+g)(x) is }x^2-2x-13[/tex]